2012
DOI: 10.3928/01477447-20120525-16
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Arthroscopic Double-bundle PCL Reconstruction Using the LARS Artificial Ligament

Abstract: The purpose of this study was to assess the outcomes of posterior cruciate ligament (PCL) reconstruction using the Ligament Augmentation and Reconstruction System (LARS) (JK Orthomedic Ltd, Dollard-des-Ormeaux, Quebec, Canada) artificial ligament. Compared with older artificial ligaments, the LARS, which has been used in Europe for 15 years, is more resistant to wear and tear, has satisfactory torsional fatigue resistance, and has good biocompatibility. The current is study included 38 double-bundle PCL recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…11,17,34 Clinical studies have reported promising outcomes for DB PCLRs, and it has been suggested that native kinematics are more closely reestablished with this technique. 6,32 In addition, kinematic investigations have reported that DB reconstructions result in decreased posterior laxity compared with SB PCLRs across a large range of motion in the knee. 29 However, because of the disparity of the current literature, neither technique has conclusively been determined to be superior.…”
mentioning
confidence: 99%
“…11,17,34 Clinical studies have reported promising outcomes for DB PCLRs, and it has been suggested that native kinematics are more closely reestablished with this technique. 6,32 In addition, kinematic investigations have reported that DB reconstructions result in decreased posterior laxity compared with SB PCLRs across a large range of motion in the knee. 29 However, because of the disparity of the current literature, neither technique has conclusively been determined to be superior.…”
mentioning
confidence: 99%
“…5 Clinically, the same controversy exists, with some authors showing good outcomes for the single-bundle approach, 7,22,24,38 while others demonstrate good results for double-bundle reconstruction. 9,41 The current study showed that surgeons could be guided toward a target point provided by an overlay system. Moreover, the overlay system helped surgeons to place the femoral tunnels closer to the anatomic insertion site for double-bundle reconstruction.…”
Section: Discussionmentioning
confidence: 65%
“…In a follow-up study lasting for 9.27 years on average, their last follow-up revealed a mean IKDC score of up to 79.32. Chen et al (5) used double-strand LARS for PCL reconstruction, and after two years operatively the average Tegner activity scores were improved to 6.0 from pre-operative 3.4 and the average Lysholm scores were raised to 91.76 from pre-operative 70.06.…”
Section: Discussionmentioning
confidence: 99%
“…LARS was rst used for ACL reconstruction and achieved excellent results. Since then, some researchers tried to use LARS to reconstruct PCL (5,6). However, few studies had compared the e cacy of LARS and hamstring tendon for the PCL reconstruction.…”
Section: Introductionmentioning
confidence: 99%